THE IMPACT OF USING POCKET BOOKS ON HUSBANDS' KNOWLEDGE, SUPPORT, AND COMPLIANCE IN THE DELIVERY PREPARATION PROCESS AT BOJONGGEDE COMMUNITY HEALTH CENTRE - Sarasati, Kadesma Fadhila Clara; HR, Teni Nurlatifah; Raksanagara, Ardini Sapatiningsih; Herawati, Yanti; Rinaldi, Andi; Sutisna, Ma'mun (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
The process from pregnancy to childbirth is a natural phase for women, during which spousal support plays a critical role. To enhance this support, a pocket guide can provide structured and accessible information for husbands. This study aims to assess the impact of using a pocket guide on husbands' knowledge, support, and compliance during childbirth preparation at the Bojonggede Health Center in Bogor Regency. A quasi-experimental method with a pre-test and post-test control group design was used. The population consisted of husbands of women in their third trimester of pregnancy, selected through total sampling. The study was conducted from May to June 2024. Data analysis using the Mann-Whitney test revealed significant effects: the pocket guide improved knowledge (p = 0.002), support (p = 0.013), and compliance (p = 0.001) in the childbirth preparation process. The N-Gain score of 56.93% indicates moderate effectiveness. These findings suggest that pocketbooks are a useful tool in improving husbands' roles in supporting their partners through childbirth. The study concludes that pocketbooks positively influence husbands' involvement and recommends their use by health workers, especially midwives, in antenatal care settings to foster greater spousal engagement during pregnancy and childbirth.